Investigating the Efficacy of Topological Methods for Optimal Sensor Placement in Water Distribution Systems - Ludovica Palma; Armando Di Nardo; Fatemeh Hatam; Giovanni Francesco Santonastaso; Michèle Prévost (Engineering proceedings, 2024)
Water-distribution networks (WDNs) are vital infrastructure that are exposed to the risk of contamination. Several factors contribute to this risk, including insufficient pressure, contamination in water storage tanks and more. Sensor systems are crucial for detecting contaminations promptly. Traditional optimization methods to define sensor locations often require resource-intensive network modeling, posing challenges for water utilities. This study applies a topological approach using betweenness centrality to address sensor placement. Various weights based on the physical structure of the network are tested. Results highlight the effectiveness of weighted topological approaches in minimizing contamination’s public health impact, with the advantage of low computational costs inherent in graph-based network representations.